The Role of the Effects of Autophagy on NLRP3 Inflammasome in Inflammatory Nervous System Diseases - Zhao, Shizhen; Li, Xiaotian; Wang, jie; Wang, Honggang (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is a stable self-sustaining process in eukaryotic cells. In this process, pathogens, abnormal proteins, and organelles are encapsulated by a bilayer membrane to form autophagosomes, which are then transferred to lysosomes for degradation. Autophagy is involved in many physiological and pathological processes. Nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome, containing NLRP3, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) and pro-caspase-1, can activate caspase-1 to induce pyroptosis and lead to the maturation and secretion of interleukin-1 β (IL-1 β) and IL-18. NLRP3 inflammasome is related to many diseases. In recent years, autophagy has been reported to play a vital role by regulating the NLRP3 inflammasome in inflammatory nervous system diseases. However, the related mechanisms are not completely clarified. In this review, we sum up recent research about the role of the effects of autophagy on NLRP3 inflammasome in Alzheimer’s disease, chronic cerebral hypoperfusion, Parkinson’s disease, depression, cerebral ischemia/reperfusion injury, early brain injury after subarachnoid hemorrhage, and experimental autoimmune encephalomyelitis and analyzed the related mechanism to provide theoretical reference for the future research of inflammatory neurological diseases.